Establishing correct matters of faith Through The Holy Quran's teaching - Mohamed, Mona AbdelKhalek (Journal of Educational and Psychological Sciences, 2018)
The aim of this research is to strengthen the role of the educator in the doctrine education; it shows the importance of linking the doctrine ( Islamic Faith) to the teaching of the Holy Quran, and that the interest in the doctrinal education is the approach of the Prophet peace be upon him and good predecessors. It also supports the educator by possible means to establish the correct doctrine through teaching the Holy Quran; As it is beneficial for the trainee to believe in certainty, supported by the evidence, not on the tradition , so that he can stand in front of what is opposed him as seditions and suspicions . Among these means are interpretation of Quran based on the doctrine of Ahl al-Sunnah wa al-Jama'ah, taking care of the causes of descent, paying great attention to the science of purposes and events, and the science of endowment and initiation. These means are enhanced for educators in the performance of doctrine education to the fullest extent.
Keywords: the correct belief; teaching the Qur'an; dogmatic education